Perilaku Komunikasi Digital Native dalam Pengungkapan Identitas Keagamaan di Media Sosial Instagram - sofia aunul (Communicology: Jurnal Ilmu Komunikasi, 2019)
The development of information technology in the past ten years has influenced communication behavior. Digital natives are a generation who are used to using gadgets in their daily lives since they were small. The emergence of social media applications such as: Facebook, Instagram, WhatsApp and others are accompanied by mobile communication devices. make someone share communication content easily simultaneously with other people both personally and in bulk (broadcast). Their self-disclosure of religious identity is demonstrated through social media applications. This study uses descriptive qualitative method that will observe the behavior of their cpmmunication for self-disclosure of their religious identity. Keywords: Communication behavior, religious identity, digital natives